Systematic Literature Review: Technology-Based and Contextual Science Literacy in Elementary School Science Education - Arika Febriana Habsari; Woro Sumarni; Nuni Widiarti; Bambang Subali (Journal of Science Education Research, 2026)
Low science literacy is one of the challenges in education in Indonesia. Various learning innovations are one of the efforts to increase students' interest and science literacy. This study aims to systematically review trends, approaches, and innovations in technology-based and contextual science learning in improving students' science literacy. The method used was a systematic literature review of 26 selected articles from various databases, which were selected using specific inclusion and exclusion criteria. The results of the analysis show that the trend of publications has been increasing since 2023 with various innovations in science literacy learning. The most widely used learning approaches include technology-based learning, outdoor learning, science experiments, social science issues, and local culture or ethnoscience. The learning innovations that have been developed include science curricula, VR media, interactive video media, E-LKPD, and so on. The conclusion of this study confirms that science literacy can be improved through various learning innovations to increase students' interest and motivation in learning science. Technology-based and contextual science learning has proven to be a strategic response to the challenge of low science literacy.